Higher risk of pre-eclampsia and other vascular disorders with artificial cycle for frozen-thawed embryo transfer compared to ovulatory cycle or to fresh embryo transfer following in vitro fertilization - Epelboin, Sylvie; Labrosse, Julie; De Mouzon, Jacques; Devaux, Aviva; Gervoise-Boyer, Marie-José; Hesters, Laetitia; Jonveaux, Philippe; Levy, Rachel; Sermondade, Nathalie; Fauque, Patricia; Pessione, Fabienne (Frontiers in Endocrinology, 2023)
Background: Risks of maternal morbidity are known to be reduced in pregnancies resulting from frozen embryo transfer (FET) compared to fresh-embryo transfer (fresh-ET), except for the risk of pre-eclampsia, reported to be higher in FET pregnancies compared to fresh-ET or natural conception. Few studies have compared the risk of maternal vascular morbidities according to endometrial preparation for FET, either with ovulatory cycle (OC-FET) or artificial cycle (AC-FET). Furthermore, maternal pre-eclampsia could be associated with subsequent vascular disorders in the offspring. Methods: A 2013-2018 French nationwide cohort study comparing maternal vascular morbidities in 3 groups of single pregnancies was conducted: FET with either OC or AC preparation, and fresh-ET. Data were extracted from the French National Health System database. Results were adjusted for maternal characteristics and infertility (age, parity, smoking, obesity, history of diabetes or hypertension, endometriosis, polycystic ovary syndrome and premature ovarian insufficiency). Results: A total of 68025 single deliveries were included: fresh-ET (n=48152), OC-FET (n=9500), AC-FET (n=10373). The risk of pre-eclampsia was higher in AC-FET compared to OC-FET and fresh-ET groups in univariate analysis (5.3% vs. 2.3% and 2.4%, respectively, P<0.0001). In multivariate analysis the risk was significantly higher in AC-FET compared to fresh-ET: aOR=2.43 [2.18-2.70], P<0.0001). Similar results were observed for the risk of other vascular disorders in univariate analysis (4.7% vs. 3.4% and 3.3 %, respectively, P=0.0002) and in multivariate analysis (AC-FET compared to fresh-ET: aOR=1.50 [1.36-1.67], P<0.0001). In multivariate analysis, the risk of pre-eclampsia and other vascular disorders were comparable in OC-FET and fresh-ET: aOR=1.01 [0.87-1.17, P= 0.91 and aOR=1.00 [0.89-1.13], P=0.97, respectively).Within the group of FET, the risks of pre-eclampsia and other vascular disorders in multivariate analysis were higher in AC-FET compared to OC-FET (aOR=2.43 [2.18-2.70], P<0.0001 and aOR=1.5 [1.36-1.67], P<0.0001, respectively). Conclusion: This large nationwide cohort study highlights the possibly deleterious role of high prolonged doses of exogenous estrogen-progesterone supplementation on gestational vascular pathologies and the protective role of the corpus luteum present in OC-FET for their prevention. Since OC-FET does not strain the chances of pregnancy, OC preparation should be advocated as first-line preparation in FET as often as possible in ovulatory women.